PEMBUATAN DAN VALIDASI TES PENGETAHUAN KESEHATAN DAN KESELAMATAN KERJA LABORATORIUM CALON GURU KIMIA - oktariani oktariani; yelfira sari; asyti febliza (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2019)
Abstract This study was conducted to create and validate the instruments test of prechemistry teacher’s knowledge about health and safety work in laboratory. This instrument will be used to obtain information about prechemistry teacher’s knowledge about health and safety work in laboratory. This research has been conducted using Research and Development (R & D) design that was developed by adopting 4D development model consisting of 4 stages: define, design, develop and dissemination. However, this research only reached the develop stage. Data analysis was performed to test the validity and reliability of the tests. Data processing was performed using IBM-SPSS 20 software. The results of this study showed that the test was valid and was feasible to implement based on the CVI value of 0.847. The reliability test of prechemistry teacher’s knowledge about health and safety work in laboratory was obtained at 0.766, its mean that the reliability of the tests was classified as in high category. Thus this instrument can be used to determine the level of prechemistry teacher’s knowledge about health and safety work in laboratory. Although there are some parts of the instrument need to be revised again. Keywords : instrument, healthy and safety work, laboratory, reliability, validity